Pengaruh Ukuran Perusahaan Dan Pertumbuhan Penjualan Terhadap Corporate Social Responsibility (Jurnal Kendali Akuntansi, 2024)
The purpose of this study is to determine the effect of company size and sales growth on corporate social responsibility in mining companies listed on the Indonesia Stock Exchange. The research time period used is 5 years, namely the 2017-2020 period. The population of this study includes all mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 9 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is multiple linear regression supported by the SPSS 25 program. The results show that company size have effect on corporate social responsibility and sales growth have no effect on corporate social responsibility. Keywords: company size, sales growth, corporate social responsibility